Thickness dependent properties of ultrathin perovskite nanosheets with Ruddlesden–Popper-like atomic stackings - Zhong, Jingxian (2022)
Ruddlesden-Popper perovskites possess a rich variety of multiple phases due to their mixed organic cations and variable layer numbers. However, the direct observation of these phases and their optical performance in ultrathin nanosheets, have rarely been reported. Here we demonstrate, through a one-pot CVD synthesis method to incorporate MA(+) and NMA(+) cations into PbI2 simultaneously, that the stackings of Ruddlesden-Popper phases with a distribution of a number of layers n can be produced within a single perovskite nanosheet. As featured by the micro-, time-resolved and temperature-dependent photoluminescence measurements, the optical properties are highly dependent on the nanosheet thickness.